2017
DOI: 10.1371/journal.pone.0176934
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed lavage cleansing of osteochondral grafts depends on lavage duration, flow intensity, and graft storage condition

Abstract: IntroductionOsteochondral allograft (OCA) transplantation is generally effective for treating large cartilage lesions. Cleansing OCA subchondral bone to remove donor marrow elements is typically performed with pulsed lavage. However, the effects of clinical and experimental parameters on OCA marrow removal by pulsed lavage are unknown. The aim of the current study was to determine the effects on marrow cleansing in human osteochondral cores (OCs) of (1) lavage duration, (2) lavage flow intensity, and (3) OC sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Remaining allogeneic marrow in the donor bone may instigate more severe immunogenic responses, particularly with larger grafts, which may also contribute to failure of integration. [38][39][40][41][42] The current SOC pretreatment of OCAs being prepared for transplantation, saline irrigation, only addresses marrow element removal. Based on translational and clinical evidence, 15,16 the OCA pretreatment protocol at our institution includes saturation of the osseous portion of the graft with autogenous BMC in an attempt to speed the process of creeping substitution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remaining allogeneic marrow in the donor bone may instigate more severe immunogenic responses, particularly with larger grafts, which may also contribute to failure of integration. [38][39][40][41][42] The current SOC pretreatment of OCAs being prepared for transplantation, saline irrigation, only addresses marrow element removal. Based on translational and clinical evidence, 15,16 the OCA pretreatment protocol at our institution includes saturation of the osseous portion of the graft with autogenous BMC in an attempt to speed the process of creeping substitution.…”
Section: Discussionmentioning
confidence: 99%
“…The marrow portion of bone allografts is allogeneic, and remaining allogeneic marrow elements may incite more severe immunogenic responses, particularly with larger grafts. [38][39][40][41][42] For the current standard of care (SOC), power irrigation with saline is used to remove marrow elements from OCAs immediately prior to implantation. Marrow element removal by pulse lavage with saline has been demonstrated to increase with irrigation duration and volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that after PL, fresh OCAs may lose from 22.6 to 46% of their marrow volume when compared with control, and up to 63% of marrow volume if previously frozen, depending on duration of lavage. 7,19 It has previously been suggested that the majority of the OCA's ability to resist compressive/tensile forces come from the osseous component of the plug. 16,17,20 However, after subjecting the 7 mm grafts to a 1-minute, normal saline lavage, these plugs demonstrated no significant differences in their compressive and tensile resistance properties (p > 0.05) (►Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Allograft empty marrow volume was found to increase from 36 to 55% after fresh OCAs were subjected to 45 to 120 second periods of PL. 7,19 The effect of this decrease in nearly half of trabecular bone volume (thought to be the primary contributor to stability) on resistance to deforming forces has not been previously evaluated.…”
mentioning
confidence: 99%